Blood flow restriction does not affect acute measures of power and fatigue during maximal cycling among women - Hoover, S.; Henderson, D. D.; Cross, J. E.; Giammalva, O. J.; Whicker, J.; Lyons, T. S.; Zolp, A.; Vidic, Z.; Hoover, D. L. (ISBS Proceedings Archive (Michigan), 2023)
While it is known that blood flow restriction (BFR) can positively affect training and rehabilitation progression timelines, the physiological basis of this intervention is not fully understood. The purpose of this study was to determine the short-term impact of BFR upon power and fatigue performance measures during maximal cycling. In this study, maximal cycling was assessed using the Wingate Anaerobic Test (WAnT). Using a counterbalanced design, fourteen female participants completed standardized BFR and non-BFR protocols while completing the WAnT. No statistically-significant differences (p = 0.05) were found between conditions for measures of peak power (PP), low power (LP) or fatigue index (FI). These findings suggest that BFR had no statistically-significant acute effect on these performance measures commonly assessed during the WAnT.